Method for preparing negative electrode active material for lithium secondary battery, negative electrode active material for lithium secondary battery and lithium secondary battery

By coating original tar or soft asphalt on the negative electrode active material precursor of the lithium-ion secondary battery and heat treatment, a negative electrode active material with a small specific surface area is prepared, which solves the problem of insufficient capacity of graphite materials in the prior art, improves the cycle life of the battery and reduces production costs.

CN114930575BActive Publication Date: 2025-03-14POHANG IRON & STEEL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080087810.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-11
Publication Date
2025-03-14
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

The negative active substance graphite of existing lithium-ion secondary batteries has a low operating voltage and theoretical capacity, which is difficult to meet the needs of electric vehicles and various application fields.

Method used

By coating the original tar or soft bitumen on the negative electrode active material precursor including Si and performing heat treatment, an negative electrode active material for lithium secondary batteries with a small specific surface area is prepared.

Benefits of technology

This method can significantly reduce the specific surface area of ​​the negative electrode active material, inhibit the formation of solid electrolyte interface, improve the cycle life characteristics of the battery, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114930575B_ABST
    Figure CN114930575B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a negative electrode active material for a lithium secondary battery, a negative electrode active material for a lithium secondary battery prepared by the method, and a lithium secondary battery comprising the negative electrode active material. The method for preparing a negative electrode active material for a lithium secondary battery comprises: a step of coating a negative electrode active material precursor comprising Si with crude tar or soft asphalt; and a step of heat treating the obtained coated product, wherein the crude tar comprises a low molecular weight component in an amount of less than 20wt% that can be removed by a distillation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a method for preparing a negative electrode active material for a lithium secondary battery, the negative electrode active material for a lithium secondary battery prepared by the method, and a lithium secondary battery comprising the negative electrode active material. Background Art

[0002] As environmental issues become an important international topic, lithium ion secondary batteries (LIBs) have attracted much attention as a new energy storage device. Compared with typical secondary battery systems such as nickel-cadmium batteries and nickel-metal hydride batteries, lithium-ion secondary batteries have higher operating voltage and energy density, and have excellent characteristics in storage effect, so they are widely used in various application fields. With the increasing demand for lithium secondary batteries with high energy density such as nickel-cadmium batteries (Ni-Cd) and nickel-metal hydride batteries, the use of silicon or silicon oxide materials with an effective capacity more than ten times that of carbon materials as negative electrode active materials of lithium ion secondary batteries has gradually increased.

[0003] Lithium-ion secondary batteries are composed of positive electrodes, negative electrodes, separators, and electrolytes. The performance of the battery is closely related to the characteristics of the structural elements. Among them, the negative electrode active material that constitutes the negative electrode has been using hard carbon / soft carbon or graphite materials as carbon materials for nearly three decades since the development of lithium-ion secondary batteries in 1991. Currently, most commercial batteries mainly use graphite materials, and various combinations of graphite compositions are used depending on the battery manufacturer.

[0004] Although the graphite material currently used as the negative electrode active material for lithium-ion secondary batteries has advantages in terms of low working voltage, stable life characteristics, efficiency, price and environmental protection, it has the disadvantage that the maximum theoretical capacity is limited to 372 mAh / g. Due to this limitation of theoretical capacity, it is difficult to ensure the mileage of electric vehicles and difficult to apply to various application fields.

[0005] Next generation materials that are being considered to overcome the capacity of graphite include oxides of various elements and Group IV elements represented by Si. Among them, Si is the most actively considered candidate element for high-capacity active materials in terms of price and versatility.

[0006] Theoretically, silicon-based negative electrode active materials have a higher capacity than commercial graphite-based negative electrode active materials by more than ten times. However, the volume change of silicon-based negative electrode active materials during filling reaches 400%, and the stress (strain) generated during discharge causes a short circuit between the collector and the collapse of the electrode itself, which has the problem of poor battery performance, and therefore has the problem of being difficult to commercialize. That is, the silicon crystal structure of silicon-based negative electrode active materials undergoes repeated electrochemical changes during charging and discharging, thereby repeatedly expanding and contracting the active material, thereby causing the collapse and deformation of the active material particles, leading to the loss of the conductive network, the expansion of local inactivity in the electrode, and the deterioration of irreversible capacity and cycle characteristics. In addition, if the formation of the solid electrolyte interface (SEI) is considered, defects (fracture) or cracks (crack) will be generated on the surface of the formed SEI due to the contraction / expansion of the electrode, and new surfaces will be exposed as defects and cracks are generated. Moreover, as charging and discharging proceed, the generation of defects and cracks is accelerated, so that the specific surface area increases while continuing to expose new surfaces. The newly exposed surface comes into contact with the electrolyte again, resulting in the formation and growth of a new SEI. Due to this repeated formation and growth phenomenon, the lithium ion diffusion path increases, the electrolyte consumption increases, the conductivity deteriorates, the Coulomb efficiency deteriorates, the lithium source is consumed, and the resistance increases, resulting in a significant deterioration in battery characteristics, and ultimately causing the battery to be unusable.

[0007] This problem also occurs when using a silicon-carbon composite active material, so a method for suppressing expansion and suppressing the continuous formation of SEI has been studied. As a method for minimizing the specific surface area basically through a high-pressure molding process and a method for suppressing mechanical expansion and controlling the specific surface area by forming an additional coating on the outside have been proposed. In other words, a method of high-density structure and a method of introducing a mechanical auxiliary structure have been proposed.

[0008] Kim of KETI proposed a scheme to form a pitch coating on the surface of the active material ("ACS applied materials & interfaces", 2016, 8, 12109-12117), which records the following advantages: by forming the pitch coating, the conductivity of the overall active material is improved, the active material is used as an electron transfer network, and the micropores in the pitch-based carbon are easy to diffuse Li + ions, and improve structural stability through the elastic properties of asphalt-based carbon coatings. In addition, CNRS in France proposed a scheme to introduce asphalt as a carbon source (resource) for silicon-carbon composite active substances, and emphasized the low price advantage of asphalt ("RSC Adv.", 2019, 9, 10546-10553).

[0009] However, in the negative electrode active material market, price competition is becoming increasingly fierce, and therefore it is necessary to minimize the cost of active materials. Summary of the invention

[0010] Technical issues

[0011] The purpose of one embodiment is to economically provide a method for preparing a negative electrode active material for a lithium secondary battery with a small specific surface area.

[0012] Another embodiment aims to provide a negative electrode active material for a lithium secondary battery prepared by the above preparation method.

[0013] Another embodiment aims to provide a lithium secondary battery including the negative electrode active material prepared by the above method.

[0014] Technical Solution

[0015] An implementation example provides a method for preparing a negative electrode active material for a lithium secondary battery, the method comprising: a step of coating a negative electrode active material precursor including Si with crude tar or soft asphalt; and a step of heat treating the obtained coated product, wherein the crude tar includes a low molecular weight component in an amount of less than 20 wt % that can be removed by a distillation process.

[0016] The weight average molecular weight (Mw) of the low molecular weight component may be 78 to 128.

[0017] In the step of coating with the raw tar or the soft asphalt, the raw tar or the soft asphalt can be added to a solvent to prepare a coating liquid with a concentration of 50wt% to 70wt%. The solvent can be N-methylpyrrolidone, dimethylformaldehyde, dimethyl sulfoxide, tetrahydrofuran, acetone or a combination thereof.

[0018] In the step of coating with the raw tar or the soft pitch, the negative electrode active material precursor and the raw tar or the soft pitch may be mixed, and then the mixture may be applied at a speed of 50 rpm to 100 rpm for 10 minutes to 60 minutes.

[0019] In one implementation example, the heat treatment step may be performed at 800°C to 950°C for 0.5 to 2 hours. In another implementation example, when performing the heat treatment step, the temperature may be raised to a final temperature of 950°C or less at a heating rate of 2°C / min to 10°C / min. In yet another implementation example, the temperature may be raised to 300°C to 400°C at a heating rate of 2°C / min to 10°C / min, maintained at the temperature for 0.5 to 2 hours, and then raised to a final temperature of 950°C or less at a heating rate of 2°C / min to 10°C / min.

[0020] Regarding a weight ratio of the negative electrode active material precursor and the raw tar or the soft pitch, the raw tar or the soft pitch may be 2 wt % to 20 wt % relative to 100 wt % of the negative electrode active material precursor.

[0021] The negative electrode active material precursor including Si may be Si, a Si-C complex, a Si oxide or a combination thereof.

[0022] Another implementation example provides a negative electrode active material for a lithium secondary battery prepared by the above method, the negative electrode active material for a lithium secondary battery comprising: a core including Si and amorphous carbon located on the surface of the core, and the specific surface area of ​​the negative electrode active material for a lithium secondary battery is 1 m2 / g to 6 m2 / g.

[0023] In one implementation example, the amorphous carbon may exist in a layer type that continuously covers the surface of the core. In another implementation example, the amorphous carbon may exist in an island type that is discontinuously located on the surface of the core.

[0024] The amorphous carbon may be soft carbon.

[0025] Yet another implementation example provides a lithium secondary battery, which includes: a negative electrode including a negative electrode active material; a positive electrode including a positive electrode active material; and a non-aqueous electrolyte.

[0026] Beneficial Effects

[0027] The method for preparing a negative electrode active material for a lithium secondary battery according to an embodiment is an economical process and can prepare an active material with a small specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] FIG. 1 is a diagram schematically showing the structure of a lithium secondary battery according to an implementation example. DETAILED DESCRIPTION

[0029] The following is a detailed description of an implementation example of the present invention. It should be noted that this is only provided as an example, and the present invention is not limited thereto, and the present invention is only limited by the scope of the appended claims.

[0030] A method for preparing a negative electrode active material for a lithium secondary battery in an embodiment includes: a step of coating a negative electrode active material precursor including Si with raw tar or soft asphalt; and a step of heat treating the obtained coated product, wherein the raw tar may include less than 20 wt % of low molecular weight components that can be removed by a distillation process.

[0031] Below, each step is described in detail.

[0032] First, a negative electrode active material precursor including Si is coated with crude tar or soft pitch.

[0033] The crude tar refers to coal tar in the state obtained in the pig iron manufacturing process in the ironmaking process. As described above, it refers to tar with a low molecular weight component content of 20 wt% or less.

[0034] The low molecular weight components are components that can be recovered by a distillation process and are components with a weight average molecular weight (Mw) of 78 to 128. The content of the low molecular weight components is 20 wt%, and can be 15 wt% to 20 wt%.

[0035] The low molecular weight components may include naphthalene, low boiling point components with a boiling point lower than that of naphthalene, and high boiling point components with a boiling point higher than that of naphthalene.

[0036] The low boiling point components with a boiling point lower than that of naphthalene may be, for example, pyridine, mesitylene, cresol, or a combination thereof, and may further include other low boiling point components. The content of the low boiling point components may be 13 wt% to 16 wt%.

[0037] The high boiling point components with a boiling point higher than that of naphthalene may be, for example, 9H-fluorene, isoquinoline, methylnaphthalene, 2-methylnaphthalene, dimethylnaphthalene, trimethylnaphthalene, or a combination thereof, and may further include other high boiling point components. The content of the high boiling point components may be 2 wt% to 7 wt%.

[0038] In particular, the crude tar is different from common tar. Among the high boiling point components, it includes 1.5 wt% to 3 wt% of methylnaphthalene, 2-methylnaphthalene, dimethylnaphthalene, trimethylnaphthalene, or a combination thereof.

[0039] The crude tar in one implementation example may include other pitch in the balance content. That is, the crude tar includes low molecular weight components and soft pitch. Generally speaking, the product after removing the low molecular weight components by distillation is called soft pitch. Therefore, the soft pitch used in the coating step refers to the component remaining after removing the low molecular weight components from the crude tar by distillation.

[0040] The negative electrode active material precursor including Si generally refers to Si-based materials used as negative electrode active materials for lithium secondary batteries, and may be, for example, Si, Si-C composite, Si oxide, or a combination thereof. At this time, the Si oxide may be SiO x (0 < x < 2). The Si-C composite may include silicon particles and crystalline carbon, and may also include silicon particles, amorphous carbon, and crystalline carbon.

[0041] Examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and burned coke, etc. Examples of the crystalline carbon include natural graphite, artificial graphite, or a combination thereof.

[0042] In one implementation example, as the negative electrode active material precursor including Si, a Si-C composite can be appropriately used, and a Si-C composite including silicon particles, amorphous carbon and crystalline carbon can be more appropriately used, because the initial efficiency and design capacity of the Si-C composite are higher than those of SiO x initial efficiency and designed capacity. At this time, relative to 100wt% of the negative electrode active material precursor, silicon may be 30wt% to 50wt%, amorphous carbon may be 20wt% to 35wt%, and crystalline carbon may be 20wt% to 35wt%. The Si-C composite including silicon particles, amorphous carbon and crystalline carbon can be formed by the following steps: after mixing Si and crystalline carbon, adding an amorphous carbon precursor to the mixture and molding it, and then carbonizing the obtained molded product to form the Si-C composite. Examples of the amorphous carbon precursor include coal asphalt, coal binder asphalt, petroleum asphalt, mesophase asphalt, tar, low molecular weight heavy oil and furan resin. In addition, the molding process can be carried out by applying 100 tons / cm 2 Up to 300 tons / cm 2 The carbonization process may be performed by heat treatment at 800°C to 950°C.

[0043] In the step of coating with the raw tar or the soft pitch, the weight ratio of the negative electrode active material precursor to the raw tar or the soft pitch is 2 wt % to 20 wt % relative to 100 wt % of the negative electrode active material precursor. When the amount of raw tar or the soft pitch falls within the range, the specific surface area of ​​the prepared negative electrode active material is significantly reduced to inhibit the formation of SEI, thereby having the advantage of improving life characteristics.

[0044] In the step of coating with the raw tar or the soft asphalt, solid or liquid raw tar can be used. That is, a coating liquid in which raw tar or soft asphalt is added to a solvent and the concentration is 50wt% to 70wt% can be used and the coating step can be implemented by a liquid method. When raw tar or soft asphalt is added to a solvent in this way, the viscosity of the raw tar or soft asphalt can be controlled, so that the coating process can be more easily implemented. In one implementation example, the concentration of the coating liquid can be 50wt% to 70wt%. When the concentration of the coating liquid falls within the range, it has a sufficient specific surface area reduction effect, but at a lower concentration, the specific surface area may not be sufficiently improved due to the effect of the volatile solvent.

[0045] The solvent may be N-methylpyrrolidone, dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, acetone, or a combination thereof.

[0046] In the step of coating with the original tar or the soft pitch, after mixing the negative electrode active material precursor and the original tar or soft pitch, the mixture may be applied at a speed of 50 rpm to 100 rpm for 10 minutes to 60 minutes. In addition, the mixing process may also be carried out for 20 minutes to 40 minutes. When the mixing process is carried out at the said speed, a sufficient coating can be formed, thus having the advantage of improving the specific surface area. When the said time is carried out, the specific surface area has a tendency to gradually decrease with the change of time. When deviating from the mixing speed and time range, the sufficient specific surface area reduction effect cannot be achieved, but instead, the opposite result of an increase in specific surface area will occur.

[0047] In addition, before the mixing process, a pre-mixing process may be further carried out.

[0048] Next, heat treatment is carried out on the obtained coated product. The step of heat treatment may be carried out at 800 °C to 950 °C for 0.5 hours to 2 hours. In another embodiment, when carrying out the step of heat treatment, the temperature can be raised to a final temperature below 950 °C at a heating rate of 2 °C / minute to 10 °C / minute, for example, raised to a final temperature of 800 °C to 950 °C. In yet another embodiment, when carrying out the step of heat treatment, the temperature can be raised to 300 °C to 400 °C at a heating rate of 2 °C / minute to 10 °C / minute once, and held at this temperature for 0.5 hours to 2 hours, and then from the temperature after the first heating, the temperature is raised to a final temperature below 950 °C at a heating rate of 2 °C / minute to 10 °C / minute, for example, raised to a final temperature of 800 °C to 950 °C for the second heating.

[0049] According to the heat treatment process, the original tar or soft pitch can be converted into amorphous carbon and located on the core surface.

[0050] The negative electrode active material prepared by this process includes: a core containing Si and amorphous carbon located on the surface of the core. The BET (Brunauer-Emmett-Teller) specific surface area may be 1 m² / g to 6 m² / g. When the BET specific surface area of the negative electrode active material falls within the said range, the formation of the surface SEI can be inhibited, and as a result, the cycle life characteristics can be improved, so it is suitable.

[0051] The core may be Si, a Si-C composite, a Si oxide, or a combination thereof. At this time, the Si oxide may be SiO x (0 < x < 2). The Si-C composite may include silicon particles and crystalline carbon, and may also include silicon particles, amorphous carbon, and crystalline carbon.

[0052] The amorphous carbon located on the surface of the core may be soft carbon converted from raw tar or soft pitch.

[0053] The amorphous carbon may exist in a layer-type continuously covering the surface of the core, or may exist in an island-type discontinuously located on the surface of the core.

[0054] The content of the amorphous carbon may be 2 wt % to 20 wt % relative to 100 wt % of the negative electrode active material. When the content of the amorphous carbon falls within the range, sufficient capacity can be exhibited and excellent cycle life characteristics can be achieved. The soft carbon achieved in the process has a very low capacity compared to Si and crystalline carbon included in the core, so when a small amount of soft carbon in the range is used to control the specific surface area, it can be suitable for performance improvement.

[0055] An implementation example provides a lithium secondary battery including a negative electrode, a positive electrode and an electrolyte.

[0056] The negative electrode may include a current collector and a negative electrode active material layer formed on the current collector and including the negative electrode active material of an implementation example.

[0057] In the negative electrode active material layer, the negative electrode active material may be included in an amount of 80 wt % to 98 wt % relative to the total weight of the negative electrode active material layer.

[0058] The negative electrode active material layer includes a binder and may further include a conductive material. In the negative electrode active material layer, the binder may be present in an amount of 1 wt% to 5 wt% relative to the total weight of the negative electrode active material layer. In addition, when a conductive material is further included, 90 wt% to 98 wt% of the negative electrode active material, 1 wt% to 5 wt% of the binder, and 1 wt% to 5 wt% of the conductive material may be used.

[0059] The binder plays a role in making the negative electrode active material particles adhere well to each other and to the current collector. As the binder, a non-aqueous binder, an aqueous binder or a combination thereof can be used.

[0060] Examples of the non-aqueous binder include ethylene-propylene copolymer, polyacrylonitrile, polystyrene, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.

[0061] Examples of the aqueous adhesive include styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, polymers including ethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol or a combination thereof.

[0062] When an aqueous binder is used as the negative electrode binder, a cellulose compound that can impart viscosity may be further included. As the cellulose compound, carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose or an alkali metal salt thereof may be mixed and used. As the alkali metal, Na, K or Li may be used. The content of the binder used may be 0.1 to 3 parts by weight relative to 100 parts by weight of the negative electrode active material.

[0063] The conductive material is used to impart conductivity to the electrode, and any conductive material that does not cause chemical changes can be used in the electrode. Examples of the conductive material include carbon materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber; metal materials such as metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or conductive materials of mixtures of these materials.

[0064] As the current collector, a current collector selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and a combination thereof can be used.

[0065] The negative electrode is formed by mixing a negative electrode active material, a binder, and a selective conductive material in a solvent to prepare an active material composition, and then coating the active material composition on a current collector. Water can be used as the solvent.

[0066] Such a method of forming a negative electrode is well known in the art, and thus a detailed description thereof is omitted in this specification.

[0067] The positive electrode includes a current collector and a positive electrode active material layer formed on the current collector and including a positive electrode active material.

[0068] The positive electrode active material may include a compound (lithiation intercalation compound) capable of reversibly intercalating and deintercalating lithium. Specifically, one or more composite oxides of metals selected from cobalt, manganese, nickel and combinations thereof and lithium may be used. As a further specific example, a compound represented by any of the following chemical formulas may be used. Li a A 1-b Xb D2(0.90≤a≤1.8,0≤b≤0.5);Li a A 1-b X b O 2-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a HAVE BEEN 1- b X b O 2-c D c (0≤b≤0.5,0≤c≤0.05);Li a HAVE BEEN 2-b X b O 4-c D c (0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b- c Co b X c D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Co b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni 1-b-c Mr b X c D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α≤2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni 1-b-c Mr b X c O 2-αT2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni b E c G d O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NeG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2) and Li a FePO4(0.90≤a≤1.8).

[0069] In the above chemical formula, A is selected from Ni, Co, Mn and combinations thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements and combinations thereof; D is selected from O, F, S, P and combinations thereof; E is selected from Co, Mn and combinations thereof; T is selected from F, S, P and combinations thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V and combinations thereof; Q is selected from Ti, Mo, Mn and combinations thereof; Z is selected from Cr, V, Fe, Sc, Y and combinations thereof; J is selected from V, Cr, Mn, Co, Ni, Cu and combinations thereof.

[0070] Of course, a compound having a coating on the surface of the compound can also be used, or the compound and the compound having a coating can be mixed and used. The coating may include at least one coating element compound selected from the oxide of the coating element, the hydroxide of the coating element, the hydroxyl oxide of the coating element, the oxygen-containing carbonate of the coating element, and the hydroxyl carbonate of the coating element. The compounds constituting these coatings may be amorphous or crystalline. As the coating element included in the coating, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof can be used. For the coating formation process, as long as these elements can be used in the compound and coated by a method that does not adversely affect the physical properties of the positive electrode active material (for example, spray coating or dip coating, etc.), any coating method can be used. The content of this aspect is fully understood by those skilled in the art, so detailed description is omitted.

[0071] In the positive electrode, the positive electrode active material may be included in an amount of 90 wt % to 98 wt % relative to the total weight of the positive electrode active material layer.

[0072] In one implementation example, the positive electrode active material layer may further include a binder and a conductive material. In this case, the contents of the binder and the conductive material may be 1 wt % to 5 wt % respectively relative to the total weight of the positive electrode active material layer.

[0073] The binder serves to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. As representative examples of the binder, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin and nylon can be used, but it is not limited thereto.

[0074] The conductive material is used to impart conductivity to the electrode, and any conductive material that does not cause chemical changes can be used in the electrode. Examples of the conductive material include carbonaceous materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber; metal materials such as metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or conductive materials of a mixture thereof.

[0075] As the current collector, aluminum foil, nickel foil, or a combination thereof may be used, but the present invention is not limited thereto.

[0076] For the positive electrode active material layer, after the positive electrode active material, the binder and the conductive material are mixed in the solvent to prepare the active material composition, the active material composition is coated on the current collector to form. This method of forming the active material layer is well known in the art, so a detailed description is omitted in this specification. As the solvent, N-methylpyrrolidone or the like can be used, but it is not limited thereto.

[0077] The electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0078] The non-aqueous organic solvent functions as a medium capable of moving ions involved in the electrochemical reaction of the battery.

[0079] As the non-aqueous organic solvent, carbonates, esters, ethers, ketones, alcohols or aprotic solvents can be used.

[0080] As the carbonate solvent, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC) etc. can be used. As the ester solvent, methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, propyl propionate, decanolide, mevalonolactone and caprolactone etc. can be used. As the ether solvent, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran etc. can be used. In addition, cyclohexanone etc. can be used as the ketone solvent. In addition, as the alcohol solvent, ethanol, isopropanol, etc. can be used, and as the aprotic solvent, nitriles such as R-CN (R is a linear, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may include a double-bonded aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, sulfolanes, etc. can be used.

[0081] The non-aqueous organic solvent may be used alone or in combination of two or more. The mixing ratio when two or more are mixed may be appropriately adjusted according to the desired battery performance, which is widely understood by those skilled in the art.

[0082] In addition, in the case of the carbonate solvent, it is preferred to mix a cyclic carbonate and a chain carbonate for use. At this time, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of 1:1 to 1:9, the electrolyte can show excellent performance.

[0083] When the non-aqueous organic solvent is mixed for use, a mixed solvent of a cyclic carbonate and a chain carbonate, a mixed solvent of a cyclic carbonate and a propionate solvent, or a mixed solvent of a cyclic carbonate, a chain carbonate and a propionate solvent can be used. As the propionate solvent, methyl propionate, ethyl propionate, propyl propionate or a combination thereof can be used.

[0084] At this time, when the cyclic carbonate and the chain carbonate or the cyclic carbonate and the propionate solvent are mixed for use, if the volume ratio is 1:1 to 1:9, the electrolyte can show excellent performance. In addition, when the cyclic carbonate, the chain carbonate and the propionate solvent are mixed for use, the volume ratio can be 1:1:1 to 3:3:4. Of course, the mixing ratio of the solvent can also be appropriately adjusted according to the desired physical properties.

[0085] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent in the carbonate-based solvent. At this time, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.

[0086] As the aromatic hydrocarbon organic solvent, an aromatic hydrocarbon compound represented by the following Chemical Formula 1 may be used.

[0087] [Chemical formula 1]

[0088]

[0089] In the chemical formula 1, R1 to R6 are the same as or different from each other and are selected from hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group, and a combination thereof.

[0090] Specific examples of the aromatic hydrocarbon organic solvent are selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, Fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene and combinations thereof.

[0091] In order to improve the battery life, the electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following Chemical Formula 2 as an additive for improving the life.

[0092] [Chemical formula 2]

[0093]

[0094] In the chemical formula 2, R7 and R8 are the same as or different from each other and are selected from hydrogen, a halogen group, a cyano group (CN), a nitro group (NO2) and a fluorinated alkyl group having 1 to 5 carbon atoms. At least one of R7 and R8 is selected from a halogen group, a cyano group (CN), a nitro group (NO2) and a fluorinated alkyl group having 1 to 5 carbon atoms, but R7 and R8 are not both hydrogen.

[0095] Representative examples of the ethylene carbonate compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, and fluoroethylene carbonate. When such an additive for improving the life is further used, its usage amount can be appropriately adjusted.

[0096] The electrolyte may further include vinyl ethylene carbonate, propane sultone, succinonitrile or a combination thereof, and the amount of the electrolyte used may be appropriately adjusted.

[0097] The lithium salt is dissolved in an organic solvent and acts as a lithium ion supply source in the battery, thereby enabling the basic operation of a lithium secondary battery. It is a substance that promotes the movement of lithium ions between the positive electrode and the negative electrode. Representative examples of such lithium salts are selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (here, x and y are natural numbers, for example, integers from 1 to 20), one or more of LiCl, LiI and LiB(C2O4)2 (lithium bis(oxalato)borate (LiBOB) are included as supporting electrolytic salts. The concentration of the lithium salt used is preferably in the range of 0.1M to 2.0M. When the concentration of the lithium salt falls within the range, the electrolyte has appropriate conductivity and viscosity, so that the electrolyte can exhibit excellent performance and can effectively move lithium ions.

[0098] Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride or a multilayer film of two or more layers thereof may be used, and of course, a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and a polypropylene / polyethylene / polypropylene three-layer separator may be used.

[0099] 1 shows an exploded perspective view of a lithium secondary battery according to an embodiment of the present invention. Although a rectangular lithium secondary battery is used as an example to illustrate an embodiment of the present invention, the present invention is not limited thereto and can be applied to batteries in various shapes such as cylindrical or pouch-shaped batteries.

[0100] 1 , a lithium secondary battery 100 of an embodiment may include an electrode assembly 40 and a housing 50. The electrode assembly 40 is formed by placing a separator 30 between a positive electrode 10 and a negative electrode 20 and winding the electrode assembly 40. The electrode assembly 40 is placed in the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated in an electrolyte (not shown).

[0101] The following examples and comparative examples of the present invention are described below. The following examples are only examples of the present invention, and the present invention is not limited to the following examples.

[0102] (Comparative Example 1)

[0103] The polycrystalline silicon is pulverized into a particle size of 200 nm or less by a wet grinder, wherein an isopropyl alcohol solvent is used.

[0104] High-purity natural graphite with a D50 of 3 μm or less is added to the prepared silicon liquid and mixed, and then a spray drying process is performed to prepare composite spheres with a size of D90 of 30 μm or less.

[0105] The prepared composite sphere and coal-based binder pitch having a D50 of 3 μm or less were placed in a mechanofusion device to prepare a composite body. At this time, the amount of Si, pitch and natural graphite used was such that Si in the prepared composite body was 37.9 wt%, pitch was 35.2 wt% and natural graphite was 26.9 wt%.

[0106] Through the pressure forming equipment at 1.8 tons / cm 2 A molded article is prepared from the prepared composite at a pressure of . The prepared molded article is subjected to a carbonization process of heat treatment at 950°C. In this carbonization process, low molecular organic matter inside is removed and the asphalt is converted into soft carbon. The prepared carbide is crushed and sieving using a jet mill so that D50 becomes about 15μm. The sieved product is used as a negative electrode active material. The BET specific surface area of ​​the negative electrode active material is 12.2㎡ / g.

[0107] (Example 1)

[0108] The sieved product prepared in Comparative Example 1 was used as a negative electrode active material precursor.

[0109] After mixing 100 wt % of the negative electrode active material precursor and 20 wt % of raw tar, the mixture was added to a planetary mixer and pre-mixed for five minutes, and then a coating process was performed at 80 rpm for 30 minutes.

[0110] The raw tar used includes 20 wt% of low molecular weight components that can be removed by a distillation process, and the low molecular weight components include pyridine, trimethylbenzene, cresol, naphthalene, methylnaphthalene, 2-methylnaphthalene, dimethylnaphthalene, trimethylnaphthalene and 9H-fluorene, wherein the total content of methylnaphthalene, 2-methylnaphthalene, dimethylnaphthalene and trimethylnaphthalene is 1.74 wt%.

[0111] The obtained coating product was subjected to heat treatment, and the temperature was raised to 950°C at a heating rate of 10°C / min, and then maintained at 950°C for one hour, thereby preparing a negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core, wherein the core includes Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon is 10wt% relative to the total amount of 100wt% of the negative electrode active material. The BET specific surface area of ​​the prepared negative electrode active material is 2.69㎡ / g.

[0112] (Example 2)

[0113] The crude tar used in Example 1 was added to N-methylpyrrolidone solvent to prepare a crude tar liquid having a concentration of 89 wt %.

[0114] The negative electrode active material precursor prepared in Example 1 and the raw tar liquid were pre-mixed for five minutes by a planetary mixer, wherein the raw tar accounted for 10 wt % relative to 100 wt % of the negative electrode active material precursor, and then a coating process was carried out by mixing at 80 rpm for 30 minutes.

[0115] The obtained coating product was subjected to heat treatment, and the temperature was raised to 950°C at a heating rate of 10°C / min, and then maintained at 950°C for one hour, thereby preparing a negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core, wherein the core includes Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the ratio of amorphous carbon derived from raw tar is 1.8wt% relative to the total amount of the negative electrode active material 100wt%. The BET specific surface area of ​​the negative electrode active material is 4.64㎡ / g.

[0116] (Example 3)

[0117] The negative electrode active material precursor 100wt% and the raw tar 20wt% were mixed, and the mixture was added to a planetary mixer and pre-mixed for five minutes, and then the coating process was mixed at 80rpm for 60 minutes. The negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core was prepared in the same manner as in Example 1, wherein the core included Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon was 2.2wt% relative to the total amount of 100wt% of the negative electrode active material. The BET specific surface area of ​​the negative electrode active material was 2.91㎡ / g.

[0118] (Example 4)

[0119] The negative electrode active material precursor and the raw tar liquid prepared in the embodiment 1 were pre-mixed for five minutes by a planetary mixer, wherein the raw tar was 20wt% relative to 100wt% of the negative electrode active material precursor, and then a coating process was carried out by mixing at 80rpm for 60 minutes, and the negative electrode active material comprising a core and soft carbon amorphous carbon arranged in layers on the surface of the core was prepared in the same manner as the embodiment 2, wherein the core comprises Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon is 2.2wt% relative to the total amount of 100wt% of the negative electrode active material. The BET specific surface area of ​​the negative electrode active material is 3.12㎡ / g.

[0120] (Example 5)

[0121] The negative electrode active material precursor 100wt% and the raw tar 20wt% were mixed, and the mixture was added to a planetary mixer and pre-mixed for five minutes, and then the coating process was mixed at 120rpm for 60 minutes. The negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core was prepared in the same manner as in Example 1, wherein the core included Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon was 2.2wt% relative to the total amount of 100wt% of the negative electrode active material. The BET specific surface area of ​​the negative electrode active material was 3.48㎡ / g.

[0122] (Example 6)

[0123] The crude tar used in Example 1 was added to N-methylpyrrolidone solvent to prepare a crude tar liquid having a concentration of 12.5 wt %.

[0124] The negative electrode active material precursor prepared in Example 1 and the raw tar liquid were pre-mixed for five minutes by a planetary mixer, wherein the raw tar accounted for 10 wt % relative to 100 wt % of the negative electrode active material precursor, and then a coating process was carried out by mixing at 80 rpm for 30 minutes.

[0125] The obtained coating product was subjected to heat treatment, and the temperature was raised to 950°C at a heating rate of 10°C / min, and then maintained at 950°C for one hour, thereby preparing a negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core, wherein the core includes Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon is 4.4wt% relative to the total amount of 100wt% of the negative electrode active material. The BET specific surface area of ​​the negative electrode active material is 5.72㎡ / g.

[0126] (Example 7)

[0127] The same method as in Example 6 was used except that the coating process was mixed at 80 rpm for 60 minutes after the five-minute premixing, thereby preparing a negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core, wherein the core includes Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon is 4.4 wt% relative to the total amount of 100 wt% of the negative electrode active material. The BET specific surface area of ​​the negative electrode active material is 5.38 m2 / g.

[0128] (Example 8)

[0129] The same method as in Example 6 was used except that the coating process was mixed at 80 rpm for 90 minutes after the five-minute premixing, thereby preparing a negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core, wherein the core includes Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon is 4.4 wt% relative to the total amount of 100 wt% of the negative electrode active material. The BET specific surface area of ​​the negative electrode active material is 5.45 m2 / g.

[0130] (Example 9)

[0131] The same method as in Example 6 was used except that the coating process was mixed at 80 rpm for 120 minutes after the five-minute premixing, thereby preparing a negative electrode active material including a core and soft carbon amorphous carbon arranged in layers on the surface of the core, wherein the core includes Si, soft carbon and graphite in a weight ratio of 37.9:35.2:26.9. At this time, the content of amorphous carbon is 4.4 wt% relative to the total amount of the negative electrode active material 100 wt%. The BET specific surface area of ​​the negative electrode active material is 4.95 m2 / g.

[0132] *Measure particle size distribution

[0133] For the negative electrode active materials of Comparative Example 1 and Examples 2 to 5, the particle sizes D1, D10, D50 and D90 were measured by a particle size analyzer (product name: Cilas 1090, manufacturing company: Cilas), and the results are shown in Table 1 below. At this time, D1 refers to the diameter of particles with a cumulative volume of 1% by volume in the particle size distribution, D10 refers to the diameter of particles with a cumulative volume of 10% by volume in the particle size distribution, D50 refers to the diameter of particles with a cumulative volume of 50% by volume in the particle size distribution, and D90 refers to the diameter of particles with a cumulative volume of 90% by volume in the particle size distribution.

[0134] In addition, the span value was calculated according to the following formula 1 based on the measured D90, D10 and D50 values, and the results are shown in the following Table 1.

[0135] [Formula 1]

[0136] Span = (D90-D10) / D50

[0137] For the negative electrode active materials of Comparative Example 2 and Examples 6 to 9, the particle sizes D1, D10, D50 and D90 were measured by a particle size analyzer (product name: Cilas 1090, manufactured by Cilas Corporation), and the results are shown in Table 2 below. In addition, after the span was obtained, the results are shown in Table 2 below.

[0138] *Measurement of BET

[0139] For the negative electrode active materials prepared according to the comparative example 1 and the embodiments 1 to 5, after degassing at 300° C. for three hours, the BET specific surface area was measured by a 3Flex device of Micromeritics based on the nitrogen gas adsorption BET method, and the results are shown in the following Table 1. When the BET value of the active material of comparative example 1 is set to 100%, the BET value ratio of the active materials of embodiments 1 to 5 is calculated in %, that is, the BET of the active material of the embodiment / the BET of the active material of comparative example 1 is calculated, and the results are shown in the following Table 1 as the BET change rate.

[0140] In addition, the BET specific surface areas of the negative electrode active materials prepared according to Comparative Example 2 and Examples 6 to 9 were measured, and the results are shown in Table 2 below. When the BET value of the active material of Comparative Example 1 is set to 100%, the BET value ratio of the active materials of Examples 1 to 5 is calculated by %, that is, the ratio of the BET of the active material of the example to the BET of the active material of Comparative Example 1 is calculated, and the results are shown in Table 1 below.

[0141] *Measure tap density

[0142] The tap density of the negative electrode active materials of Comparative Example 2 and Examples 6 to 9 was measured by the ISO3953 method, and the results are shown in Table 1 below.

[0143] [Table 1]

[0144]

[0145] [Table 2]

[0146]

[0147]

[0148] As can be seen from Table 1 above, the span values ​​of Examples 1 to 5 coated with raw tar are smaller than the span value of Comparative Example 1 not coated with raw tar, and BET is significantly improved, and it can be seen that the active material particles are controlled to have a uniform particle size. In particular, it can be seen that the span values ​​and BET change rates of Examples 1, 3 and 5 coated with tar by dry coating are smaller than the span values ​​and BET change rates of Examples 2 and 4 coated with tar by wet coating, and thus the effect is more excellent.

[0149] Furthermore, it is found that among Examples 1, 3, and 5 which were implemented by the dry coating method, the BET value of Example 1 which implemented the mixing coating process for 30 minutes was the smallest.

[0150] In addition, it can be seen from the above Table 1 that the span values ​​of Examples 1 to 5 coated with raw tar are smaller than that of Comparative Example 1 not coated with raw tar, and the BET is reduced.

[0151] Moreover, it can be seen from Table 2 above that the span values ​​of the active materials of Examples 8 and 9 are smaller than the span value of Comparative Example 2, thereby preparing a uniform active material. As a result, when the negative electrode is prepared using the active material, the packing density can be increased, so it can be predicted that a negative electrode with a higher capacity can be prepared. However, it can be confirmed that the results of Examples 1 to 5 in which the input amount of raw tar is increased to 20% in Table 1 are not sufficiently improved in BET value compared with the case where the input amount of raw tar is 10% shown in Table 2, and are relatively poor in terms of particle size uniformity. This result is presumed to be the result obtained because the soft carbon derived from the input raw tar remains in the electrode active material particles.

[0152] The present invention is not limited to the above-mentioned embodiments, but can be prepared in a variety of different forms. Those skilled in the art of the present invention should understand that the present invention can be implemented in other specific forms without changing the technical ideas and essential technical features of the present invention. Therefore, it should be understood that the above-mentioned embodiments are illustrative in all aspects, rather than restrictive.

Claims

1. A method for preparing a negative electrode active material for a lithium secondary battery, comprising: A step of coating a negative electrode active material precursor including Si with raw tar; and The step of heat treating the obtained coating product, wherein: The raw tar includes 15 wt % to 20 wt % of low molecular weight components that can be removed by a distillation process. and the weight average molecular weight of the low molecular weight component is 78 to 128, As for the weight ratio of the negative electrode active material precursor to the raw tar, relative to 100wt% of the negative electrode active material precursor, the raw tar is 2wt% to 20wt%, And in the step of coating with the raw tar, after the negative electrode active material precursor and the raw tar are mixed, the mixture is applied at a speed of 50 rpm to 100 rpm for 10 minutes to 60 minutes.

2. The method for preparing a negative electrode active material for a lithium secondary battery according to claim 1, wherein: In the step of coating with the raw tar, a coating liquid is used in which the raw tar is added to a solvent at a concentration of 50 wt % to 70 wt %.

3. The method for preparing a negative electrode active material for a lithium secondary battery according to claim 2, wherein: The solvent is N-methylpyrrolidone, dimethyl formaldehyde, dimethyl sulfoxide, tetrahydrofuran, acetone or a combination thereof.

4. The method for preparing a negative electrode active material for a lithium secondary battery according to claim 1, wherein: The heat treatment step is performed at 800° C. to 950° C. for 0.5 hour to 2 hours.

5. The method for preparing a negative electrode active material for a lithium secondary battery according to claim 1, wherein: When performing the heat treatment step, the temperature is increased at a rate of 2° C. / min to 10° C. / min to a final temperature of 800° C. to 950° C.

6. The method for preparing a negative electrode active material for a lithium secondary battery according to claim 1, wherein: When implementing the heat treatment step, the temperature is increased to 300°C to 400°C at a heating rate of 2°C / min to 10°C / min, maintained at this temperature for 0.5 hour to 2 hours, and then increased to a final temperature of 800°C to 950°C at a heating rate of 2°C / min to 10°C / min for a second time.

7. The method for preparing a negative electrode active material for a lithium secondary battery according to claim 1, wherein: The negative electrode active material precursor including Si is Si, Si-C complex, Si oxide or a combination thereof.

8. A negative electrode active material for a lithium secondary battery, prepared by the method according to any one of claims 1 to 7, the negative electrode active material for a lithium secondary battery comprising: A core comprising Si and amorphous carbon on a surface of the core, The specific surface area of ​​the negative electrode active material for lithium secondary battery is 1m 2 / g to 6m 2 / g, The specific surface area is a BET specific surface area measured by a nitrogen gas adsorption BET method after degassing the negative electrode active material at 300° C. for 3 hours.

9. The negative electrode active material for lithium secondary battery according to claim 8, wherein The amorphous carbon exists in a layer form continuously covering the surface of the core.

10. The negative electrode active material for lithium secondary battery according to claim 8, wherein The amorphous carbon exists in the form of islands discontinuously located on the surface of the core.

11. The negative electrode active material for lithium secondary battery according to claim 8, wherein The amorphous carbon is soft carbon converted from raw tar.

12. A lithium secondary battery comprising: A negative electrode comprising the negative electrode active material according to any one of claims 8 to 11; A positive electrode including a positive electrode active material; and Non-aqueous electrolytes.

Citation Information

Patent Citations

  • Artificial graphite lithium ion battery anode material and preparation method thereof

    CN103887502A

  • Negative active material for rechargeable lithium battery, method of preparing same and rechargeable lithium battery including same

    US20160211514A1